Prediction of Damage and Remaining Life of Yogyakarta-Bawen Toll Road Pavement with Elastic and Viscoelastic Approaches - Tolab, Laziqoh Zahatul; Fauziah, Miftahul (Rekayasa Sipil, 2024)
Toll roads are one of the infrastructure development targets in Indonesia to speed up traffic and vehicle travel times. This paper analyzes the flexible pavement structure of the Yogyakarta-Bawen Toll Road. It predicts damage and residual values using elastic and viscoelastic approaches based on MDPJ Bina Marga 2017 using the KENPAVE Program. The recommended design alternative is pavement with a layer of AC-WC 40 mm, AC-BC 60 mm, Base AC 180 mm, and LPA 300 mm. This alternative is predicted to be able to serve load repetitions in the elastic approach of 432,857,828 ESAL until fatigue cracking occurs, 215,176,089 ESAL until rutting occurs, and 136,575,580 ESAL until permanent deformation occurs. Analysis using the viscoelastic approach can provide load repetitions of 153,304,378 ESAL until fatigue cracking occurs, 47,014,109 ESAL until rutting occurs, and 71,859,938 ESAL until permanent deformation occurs. Based on the elastic approach, the pavement's service life is 33 years, with initial damage in the form of permanent deformation. In comparison, the viscoelastic approach has a service life of 22.7 years, with initial damage in the form of rutting.